2013
DOI: 10.4236/msa.2013.410074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Microwave Infrared Thermography and CO<sub>2</sub> Laser Infrared Thermography in Defect Detection in Applications with CFRP

Abstract: This paper presents two infrared thermography methods with CO 2 Laser excitation and microwave excitation applied to defect detection in CFRP. The tests were conducted with two specimens, one with defect, and another one without defect. On two concrete plates 40 cm × 40 cm × 4.5 cm were reinforced by CFRP; the defects were made by the absence of adhesive on an area 10 cm × 10 cm. The specimens were heated by microwave, generated by a commercial magnetron of 2.45 GHz and guided by a pyramidal horn antenna, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Clearly, defect can be found in the middle of the sample. The absence of adhesive made it hotter than other area without defect [17]. …”
Section: Figure 3 the Microwave Thermography Setup In (A) Newcastle mentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, defect can be found in the middle of the sample. The absence of adhesive made it hotter than other area without defect [17]. …”
Section: Figure 3 the Microwave Thermography Setup In (A) Newcastle mentioning
confidence: 99%
“…The antenna was placed in the 45° direction. Thermograms were recorded at 1 Hz by a computer, synchronized to the infrared camera, using the ALTAIR program [17]. The specimen was heated with a power of 360 W for 150 s. The tests on both samples (with defect, and without defect) had the same procedure.…”
Section: Figure 3 the Microwave Thermography Setup In (A) Newcastle mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermal stimulations applied from the external surface limit the auscultation depth or impose long-term tests. This paper aims to present the development of a new active infrared thermography method based on a microwave excitation system [3]. Compared to other sources traditionally used in active infrared thermography, the microwaves can propagate into the volume of a concrete element.…”
Section: Introductionmentioning
confidence: 99%
“…Keo et al [53] used a commercial 2.45 GHz magnetron and an IR camera to detect a defect (absence of adhesive) in a CFRP plate. A 360 W microwave signal was applied to heat the sample for 150 s. It was found that the defect area was hotter than the non-defect area.…”
Section: Integration With Other Ndtmentioning
confidence: 99%